The use of insulin in treatment for inpatients with diabetes in Can Tho, Vietnam 2017 to 2020. - Duyen Thi My Huynh; Duyen Quang Loc Vo; Van De Tran (GarVal Editorial Ltda., 2022)
Context: Diabetes is a dangerous chronic disease with a rapidly increasing rate of hospitalization and death. Patients with uncontrolled diabetes are prone to dangerous acute and chronic complications. Aims: To determine the characteristics of insulin use and factors related to blood glucose control in inpatients with diabetes at the Department of General Medicine-Can Tho University of Medicine and Pharmacy Hospital. Methods: A cross-sectional descriptive study on 390 medical records of inpatients with diabetes at the Department of General Medicine-Can Tho University of Medicine and Pharmacy Hospital from 2017 to 2020. Results: Most hospitalized patients had poor control of HbA1c (52.3%). During the treatment, patients were regularly tested for blood sugar and 3.8% of them had hypoglycemic test patterns. The rate of good control of fasting blood glucose at hospital discharge accounted for the majority with 67.4%. Regarding the insulin use, premixed insulin was used the most with a rate of 77.5% and insulin monotherapy accounted for 73.3%. The mean insulin dose was 23.4 ± 10.6 UI/day. Factors such as HbA1c index, comorbidities, and insulin doses were associated with poor glycemic control of inpatients. Conclusions: The selection of insulin use in inpatients with diabetes was consistent with global guidelines and actual situations at the hospital. It is necessary to monitor factors such as HbA1c index, comorbidities, and insulin doses because these factors are associated with poor glycemic control of inpatients.